Tuberculosis of breast: an Indian scenario - Samal, Debasish; Sahoo, Rashmiranjan; Maity, Krishnendu; Patra, Kalpita; Abdullah, Umar (International Surgery Journal, 2018)
Background: Tuberculosis of breast is quite rare in relation to all breast pathology that we encounter in our daily practice. Ever since it was first described in 1829 many reports have been published. There has been an increasing incidence since the resurgence of AIDS. Methods: This study was done to see the incidence, presentation and investigative modality of tuberculosis of breast in our hospital. Results: A total of 986 patients out of which 585 were fibrocystic breast disease, 238 were malignant, 84 cases presented as abscess, followed by 45 cases as galactocele. 34 cases were diagnosed as tuberculosis of breast. Presentation of tuberculosis of breast was lump 19cases. 9 cases presented as abscess of breast, 4 cases had discharging sinus out of which 2 had developed them after being operated elsewhere for benign breast lump and abscess. Core needle biopsy was done in 4 cases with 2 cases coming out to be positive. Incisional biopsy was done on 2 cases which had come with mutilated breasts and they were positive for tuberculosis. 2 patients underwent excision of small lump diagnosed as fibroadenoma on FNAC, which came out as tuberculosis on biopsy. FNAC of the axillary lymph node showed a positivity rate of 43%. 9 cases were negative. Conclusions: Thus, breast lesions has to be dealt with carefully keeping in mind tuberculosis of breast, as it is a potentially curable disease and we can avoid a lot of morbidity if we can diagnose and start early ATT.